2007
DOI: 10.1111/j.1600-6143.2007.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hormone Resuscitation on Cardiac Function and Hemodynamics in a Porcine Brain-Dead Organ Donor Model

Abstract: We compared the effects of hormone resuscitation (HR) with a norepinephrine-based protocol on cardiac function, hemodynamics and need for vasopressor support after brain death in a porcine model. Following brain death induction, animals were treated with norepinephrine and fluids for 3 h. In the following 3 h, they continued on norepinephrine and fluids (control) or received additional HR (triiodothyronine, methylprednisolone, vasopressin, insulin). Data were collected pre-brain death, 3 and 6 h post-brain dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Use of standardized donor maintenance protocols, which include hormonal resuscitation, have increased the number of organs procured (15). Animal studies have demonstrated a benefit in cardiac contractility and hemodynamics (16). However, in a recent prospective clinical study (17,18), hormonal resuscitation did not increase the number of suitable donors, but the substitution of norepinephrine with vasopressin did confer some benefit.…”
mentioning
confidence: 97%
“…Use of standardized donor maintenance protocols, which include hormonal resuscitation, have increased the number of organs procured (15). Animal studies have demonstrated a benefit in cardiac contractility and hemodynamics (16). However, in a recent prospective clinical study (17,18), hormonal resuscitation did not increase the number of suitable donors, but the substitution of norepinephrine with vasopressin did confer some benefit.…”
mentioning
confidence: 97%
“…To correct the endocrinopathies of the donor, a combination hormone therapy with vasopressin, thyroid hormones, and methylprednisolone has been used to increase the likelihood of successful organ transplantation [18][19][20]. We were able to maintain adequate serum sodium level and urine output while using vasopressin, but they worsened once vasopressin was discontinued.…”
Section: Discussionmentioning
confidence: 94%
“…We used pigs whose body weight was close to that of adult humans. All donor animals were subjected to brain death and managed for 6 h with a protocol incorporating 'combined hormone resuscitation', which has been shown to improve heart function and donor hemodynamics in both animal models and human subjects (16,(25)(26)(27)(28), and which has been recommended for human donor management (11,29 (6,31). In this study, we chose to combine cariporide with GTN for a number of reasons.…”
Section: In This Study Lvsw After Transplantation In the Presence mentioning
confidence: 99%